Efektivitas Pemberian Insentif Badan Musyawarah Guru Al-Qur’an (BMGQ) Kecamatan Nongsa oleh Pemerintah Kota Batam Tahun 2024 - Annisa Arrum; Kustiawan Kustiawan; Khairi Rahmi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The incentive program for Al-Qur'an Education Park (TPQ) teachers in Batam City is part of a regional policy aimed at supporting the role and function of Al-Qur'an teachers in fulfilling Al-Qur'an literacy certification and basic religious understanding for elementary and secondary school students. This program has been implemented since 2009 and has experienced a gradual increase in incentive values until 2024. However, in Nongsa District, the implementation of this program still faces several obstacles. Identified problems include delays in fund distribution, inaccurate data verification, and inaccurate targeting of incentive recipients. This study aims to analyze the effectiveness of the incentive program managed by the Al-Qur'an Teacher Consultative Body (BMGQ) of Nongsa District by the Batam City Government. The research method used is qualitative, with data collection techniques through in-depth interviews, documentation, and observation. The results show that this program has had a positive impact, especially in increasing teachers' teaching enthusiasm, helping their economy, and maintaining the sustainability of Al-Qur'an education in the region. However, the effectiveness of program implementation is not yet optimal. Obstacles identified include a lack of publicity regarding the program's objectives to the community and beneficiaries, limited incentive recipient quotas, the lack of a real-time data monitoring system, and delays in the document signing process (amprah), which has delayed incentive disbursement. Therefore, ongoing evaluation by the local government and the BMGQ (Regional Teachers' Association) is necessary to ensure that incentive distribution is more targeted, equitable, and in line with the program's initial objectives, so that all TPQ teachers in Nongsa District can experience maximum benefits.